HUBUNGAN KUALITAS LAYANAN, KEPERCAYAAN, DAN LOYALITAS DALAM MEMBANGUN BRAND EQUITY RUMAH SAKIT BERBASIS PASIEN - Valencia Imelda Triastuti; Masyitoh Basabih (Jurnal Medika Hutama, 2023)
Hospital is a health institution that provides complete individual health services. A high level of brand equity, especially in healthcare organizations increases customer satisfaction, their rebates, and also the level of loyalty, which is a key role that brands play in business success. This research is to identify the role of service, trust, and loyalty in the progress of hospital brand equity. A literature search in this systematic review was conducted on 3 (three) databases: PubMed, Cochrane, Embase Google Scholar, published in 2013 until 2023. Selection of literature based on predefined inclusion and exclusion criteria. This systematic review identified 13 studies that examined service quality, trust, and loyalty in building patient-based brand equity. Service quality has a positive impact on customer loyalty, and customer loyalty has a significant positive relationship with brand equity. The quality of service, both services and facilities, has a significant effect on patient trust and satisfaction. Improving service quality by paying attention to various aspects of both services and facilities has an impact on patient trust and loyalty to the hospital. Patient loyalty has an impact on brand equity.